The Role of EBV-Encoded LMP1 in the NPC Tumor Microenvironment: From Function to Therapy - Lo, Angela Kwok-Fung; Dawson, Christopher W.; Lung, Hong Lok; Wong, Ka-Leung; Young, Lawrence S. (Frontiers in Oncology, 2021)
Nasopharyngeal carcinoma (NPC) is closely associated with Epstein-Barr virus (EBV) infection. It is also characterized by heavy infiltration with non-malignant leucocytes. The EBV-encoded latent membrane protein 1 (LMP1) is believed to play an important role in NPC pathogenesis by virtue of its ability to activate multiple cell signalling pathways which collectively promote cell proliferation and survival, angiogenesis, invasiveness, and aerobic glycolysis. LMP1 also affects cell-cell interactions, antigen presentation, and cytokine and chemokine production. Here, we discuss how LMP1 modulates local immune responses that contribute to the establishment of the NPC tumour microenvironment. We also discuss strategies for targeting the LMP1 protein as a novel therapy for EBV-driven malignancies.